High-weather-resistance titanium dioxide as well as preparation method and application thereof
By reacting with tanninic acid to modify and graft nanobarium sulfate, the problem of poor weather resistance in coatings and plastics was solved, and a high weather resistance and low cost preparation of modified titanium dioxide was achieved, which significantly improved its stability and Service life.
Patent Information
- Application Number
- CN202411297965.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing titanium dioxide is poor in weather resistance due to photosensitive when used in coatings and plastics. The existing surface coating method is costly and complex in process, and has limited effect.
Titanium dioxide is modified by reacting with tanninic acid to form chemical bonds and grafting nanobarium sulfate on its surface, combining 3-glycidyl ether oxypropyl triethoxysilane to improve the dispersion and weathering resistance of titanium dioxide.
It significantly improves the stability and service life of titanium dioxide, enhances its weather resistance and optical properties, reduces production costs, and realizes the production of environmentally friendly and energy-saving materials.
Smart Images

Figure BDA0005046680420000051 
Figure BDA0005046680420000071 
Figure BDA0005046680420000072
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium dioxide preparation, and specifically relates to high-weather-resistant titanium dioxide and a preparation method and application thereof. Background Art
[0002] In modern industry and daily life, the fields of coatings, plastics, paper, cosmetics and medicine have increasingly higher requirements for the weather resistance of materials. Weather resistance refers to the ability of materials to resist adverse factors such as ultraviolet rays, oxidation, temperature changes and microbial erosion in the natural environment.
[0003] Titanium dioxide (TiO2) is a widely used white pigment and photocatalyst, and is widely used due to its high refractive index, chemical stability and photocatalytic activity. However, titanium dioxide itself is photosensitive and can catalyze chemical reactions. When titanium dioxide is used in coatings and plastics, such reactions will cause the product color to turn yellow and the performance to deteriorate, limiting its use in high weather resistance applications.
[0004] In order to improve the weather resistance of titanium dioxide, the existing method is to carry out surface coating treatment on titanium dioxide. Metal oxide films such as silicon dioxide, aluminum oxide, and zirconium dioxide are coated on the surface of titanium dioxide particles to reduce the photostability of titanium dioxide and improve the weather resistance of the product. These methods have improved the performance of titanium dioxide to a certain extent, but there are still problems such as high cost, complicated process or limited effect.
[0005] The focus of the present invention is to provide a simple preparation method to modify titanium dioxide. Through this innovative modification method, the stability and service life of titanium dioxide are significantly improved while maintaining or enhancing its original optical and chemical properties. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention aims to provide a titanium dioxide with high weather resistance and a preparation method, and to overcome the problem of poor weather resistance of the final product caused by the sensitivity of titanium dioxide to light by coating and modifying the titanium dioxide surface through a simple process flow.
[0007] To achieve the above object, the present invention discloses the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing highly weather-resistant titanium dioxide, comprising the following steps:
[0009] S1. Mix nano-titanium dioxide and water to obtain a suspension, add a dispersant, and stir to mix evenly to obtain a titanium dioxide dispersion;
[0010] S2. Tris(hydroxymethyl)aminomethane is dissolved in the titanium dioxide dispersion, and hydrochloric acid solution is slowly added and mixed until the pH of the titanium dioxide dispersion is adjusted to 8.5-9 to obtain a mixed titanium dioxide dispersion;
[0011] S3. Take tannic acid and add it to the mixed titanium dioxide dispersion of step S2, stir at a temperature of 25-30 ° C, react for 12-24h, centrifuge solid-liquid separation, separate the solid residue A with water several times, vacuum dry, grind into powder to obtain tannic acid - titanium dioxide;
[0012] Tannic acid exists in the bark of trees and a variety of fruits. It is widely available and inexpensive. Its surface is rich in active groups and is a good functional material. Tannic acid reacts with the hydroxyl groups on the surface of titanium dioxide to form chemical bonds, thereby modifying the surface of titanium dioxide. This modification can improve the dispersibility of titanium dioxide and enhance its compatibility with the substrate. Tannic acid contains multiple phenolic hydroxyl groups, which can capture free radicals, thereby improving the weather resistance of the material and reducing the damage to the material by ultraviolet rays and oxidation. The modified titanium dioxide (tannic acid-titanium dioxide) has better thermal and chemical stability, which helps to improve the quality and service life of the final product.
[0013] S4. Take tannic acid-titanium dioxide and add it to an ethanol aqueous solution with a concentration of ≥95 v / v%, and add 3-glycidyloxypropyl triethoxysilane to dissolve evenly. At a temperature of 60-70 ° C, slowly add nano-barium sulfate and stir for 30-60 minutes. After completion, centrifuge the solid-liquid separation, and wash the separated solid slag B with water several times, vacuum dry, and grind into powder to obtain a modified high weather-resistant titanium dioxide;
[0014] The mass ratio of the tannic acid-titanium dioxide, 3-glycidyloxypropyltriethoxysilane and nano-barium sulfate is 1:(0.2-0.5):(1.6-1.8);
[0015] Barium sulfate is a white pigment with high whiteness, low wear index, low viscosity and high stability. It has excellent UV blocking properties, good sun resistance and weather resistance. It is an ideal raw material for partially replacing titanium dioxide. It can absorb harmful rays such as X-rays and gamma rays. Grafting barium sulfate onto the surface of titanium dioxide through coupling can improve the weather resistance of the final product. In addition, the addition of barium sulfate can change the rheological properties of the mixture.
[0016] Preferably, the nano titanium dioxide is rutile titanium dioxide with a particle size of 200-300 nm.
[0017] Preferably, in step S1, nano titanium dioxide is mixed with water to obtain a suspension having a material-water ratio of 1.2-2.0 g / L, a dispersant is added in an amount of 0.6-1.0 g / L, and the mixture is stirred and mixed uniformly at room temperature and 200-300 r / min to obtain a titanium dioxide dispersion.
[0018] Preferably, in step S2, tris(hydroxymethyl)aminomethane is dissolved in the titanium dioxide dispersion at an addition amount of 1.0-1.2 g / L, and a hydrochloric acid solution with a concentration of 2.5-3.65 g / L is slowly added and mixed until the pH of the titanium dioxide dispersion is adjusted to 8.5-9.
[0019] Preferably, in step S3, tannic acid is added to the mixed titanium dioxide dispersion in step S2 in an amount of 2-3 g / L, and stirred at a speed of 500-800 r / min and a temperature of 25-30° C. to react for 12-24 hours.
[0020] Preferably, in step S4, tannic acid-titanium dioxide is added to an ethanol aqueous solution with a concentration of ≥95 v / v%, at which the solid-liquid ratio is 1.0-1.5 g / L, and 3-glycidyloxypropyltriethoxysilane is added, and stirred for 30-60 min at room temperature and a speed of 200 r / min to dissolve evenly, the speed is increased to 500 r / min, the temperature is increased to 60-70°C, and nano-barium sulfate is slowly added while stirring. After the addition is completed, the speed is increased to 1000 r / min, and stirring is continued for 30-60 min.
[0021] Preferably, in steps S3 and S4, the water used in the multiple washings is deionized water, and the solid slag A is washed until the conductivity of the aqueous solution is ≤100 μS / cm, and the solid slag B is washed until the conductivity of the aqueous solution is ≤50 μS / cm.
[0022] More preferably, the dispersant is at least one of sodium hexametaphosphate, sodium dihydrogen phosphate, calcium silicate and sodium silicate.
[0023] In a second aspect, the present invention provides a highly weather-resistant titanium dioxide prepared by the method described in the first aspect.
[0024] In a third aspect, the present invention provides use of the highly weather-resistant titanium dioxide described in the second aspect in the preparation of coatings, paints and / or plastics with high weather resistance.
[0025] Beneficial effects of the present invention:
[0026] 1. The modified titanium dioxide provided by the present invention has good weather resistance and yellowing resistance, and has better weather resistance than the highly weather-resistant titanium dioxide on the market;
[0027] 2. The preparation method of the modified titanium dioxide provided by the present invention has a simple process, stable process, high production efficiency, low cost, and no pollution, which is conducive to the production and promotion of environmentally friendly and energy-saving materials. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0030] The present invention is further described in the following specific embodiments.
[0031] In the present invention:
[0032] Nano Titanium Dioxide ① : Rutile titanium dioxide, with a particle size of 200-300 nm, purchased from Beijing Dekedaojin Technology Co., Ltd.;
[0033] Nano Titanium Dioxide ② : Rutile titanium dioxide, with a particle size of 15-50 nm, purchased from Ningbo Jiwei Nano New Material Technology Co., Ltd.;
[0034] Tannic acid: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0035] Levodopa: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0036] Catechol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0037] 3-Glycidyloxypropyltriethoxysilane: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0038] Aminopropyltrimethoxysilane: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0039] Nano barium sulfate: particle size is 40-50nm, specific surface area is 20-40m 2 / g, purchased from Beijing Dekedao Gold Technology Co., Ltd.;
[0040] Sodium hexametaphosphate: purchased from Sichuan Lanjian Chemical (Group) Co., Ltd.;
[0041] Sodium dihydrogen phosphate: purchased from Sichuan Lanjian Chemical (Group) Co., Ltd.;
[0042] Calcium silicate: purchased from Shandong Lianke Technology Co., Ltd.
[0043] Sodium silicate: purchased from Shandong Lianke Technology Co., Ltd.
[0044] The remaining raw materials and reagents are commercially available.
[0045] Preparation of Examples 1-4:
[0046] Step (1), taking nano titanium dioxide ① Mix with water to obtain a suspension with a material-water ratio of 1.2-2.0 g / L, add a dispersant (sodium hexametaphosphate, sodium dihydrogen phosphate, calcium silicate, sodium silicate) at an addition amount of 0.6-1.0 g / L, stir and mix evenly at room temperature and 200-300 r / min to obtain a titanium dioxide dispersion;
[0047] Step (2), dissolving tris(hydroxymethyl)aminomethane in a titanium dioxide dispersion at an amount of 1.0-1.2 g / L, and slowly adding a hydrochloric acid solution at a concentration of 2.5-3.65 g / L to mix evenly until the pH value of the solution is adjusted to 8.5-9; adding tannic acid in an amount of 2-3 g / L, stirring at a speed of 500-800 r / min and a temperature of 25-30° C., reacting for 12-24 hours, centrifuging for solid-liquid separation, and washing the separated solid slag A with deionized water for multiple times until the conductivity of the aqueous solution of the solid slag A is ≤100 μS / cm, vacuum drying, and grinding into powder to obtain titanium dioxide with surface modified tannic acid (tannic acid-titanium dioxide);
[0048] Step (3), adding tannic acid-titanium dioxide to an ethanol aqueous solution with a concentration of ≥95 v / v%, wherein the solid-liquid ratio is 1.0-1.5 g / L, and adding 3-glycidyloxypropyltriethoxysilane, stirring for 30-60 min at room temperature and a speed of 200 r / min to dissolve evenly, increasing the speed to 500 r / min, increasing the temperature to 60-70° C., slowly adding nano-barium sulfate, stirring while adding, and increasing the speed to 1000 r / m after the addition is completed. in, stirring continuously for 30-60 min, wherein the mass ratio of tannic acid-titanium dioxide, 3-glycidyloxypropyltriethoxysilane and nano-barium sulfate is 1:(0.2-0.5):(1.6-1.8), after completion, centrifugal solid-liquid separation is completed, and the separated solid slag B is washed with deionized water for multiple times until the conductivity of the solid slag B aqueous solution is ≤50μS / cm, vacuum dried, and ground into powder to obtain modified titanium dioxide (barium sulfate-tannic acid-titanium dioxide).
[0049] The specific parameters are shown in Table 1.
[0050] Table 1 Preparation parameters of Examples 1-4
[0051]
[0052] Preparation of Comparative Examples 1-5
[0053] Comparative Example 1: Tannic acid was replaced with L-dopa and catechol in a mass ratio of 2:1 and an addition concentration of 2.5 g / L. The remaining steps were the same as those in Example 2.
[0054] Comparative Example 2: The 3-glycidyloxypropyltriethoxysilane in step (3) was replaced with aminopropyltrimethoxysilane, and the remaining steps were the same as those in Example 2;
[0055] Comparative Example 3: The nano titanium dioxide in step (1) ① Replaced with nano titanium dioxide ② , the remaining steps are the same as those in Example 2;
[0056] Comparative Example 4: The mass ratio of tannic acid-titanium dioxide, 3-glycidyloxypropyltriethoxysilane and nano-barium sulfate in step (3) was adjusted to 1:1:1, and the remaining steps were the same as those in Example 2;
[0057] Comparative Example 5: The nano-barium sulfate in step (3) is replaced with nano-barium sulfate with an average particle size of 100 nm (commercially available), and the remaining steps are the same as those in Example 2.
[0058] Performance Testing
[0059] Acid solubility test:
[0060] The modified titanium dioxide samples prepared in the examples and comparative examples were tested for acid solubility. The acid solubility results are shown in Table 1.
[0061] The acid solubility test method is as follows: add 0.2g titanium dioxide to 10mL 98% sulfuric acid, ultrasonically disperse for 1 minute, and then dissolve at 175-180℃ for 1 hour. After taking out the sample and cooling it to room temperature, add water to make it 100mL, filter it, take 10mL of the filtrate with a pipette, add 10mL 30% hydrogen peroxide solution, and dilute it to 100mL with 10% sulfuric acid solution. Leave it for 1 hour, test the absorbance of the solution at 410nm, and calculate the corresponding amount of titanium dioxide dissolved by referring to the standard curve.
[0062] Table 2 Acid solubility of the embodiments and comparative examples
[0063] Test samples Acid solubility / % Example 1 5.16 Example 2 4.77 Example 3 5.03 Example 4 5.11 Comparative Example 1 7.29 Comparative Example 2 13.72 Comparative Example 3 14.31 Comparative Example 4 7.83 Comparative Example 5 10.64
[0064] Artificial accelerated aging test:
[0065] Examples 1-4 and Comparative Examples 1-5 were made into paint films (resin: acrylic acid), and aged for 2 months (1500 h) in an artificial aging box (ATLAS Ci3000+ xenon lamp aging tester / sunlight color fastness tester). The aging results were expressed in terms of gloss loss rate and yellowing variable. The weather resistance of the modified titanium dioxide was evaluated and compared with the highly weather-resistant titanium dioxide products on the market. The results are shown in Tables 3 and 4.
[0066] Table 3 Gloss loss rate of coating after artificial aging
[0067]
[0068] Note: Light loss rate / % = (L1-L2) / L1×100%.
[0069] Table 4 Yellowing variation of coating after artificial aging
[0070]
[0071] Note: Yellow variable = b1-b2.
[0072] Result analysis:
[0073] According to the results in Tables 3 and 4, the coating films of Examples 1, 2, 3, and 4 showed lower gloss loss and yellowing after artificial aging, indicating that the modified titanium dioxide provided by the present invention has better weather resistance and yellowing resistance, and has better weather resistance than the highly weather-resistant titanium dioxide on the market.
[0074] The coating films of Comparative Examples 1-5 had higher gloss loss and yellowing after artificial aging, showing poorer weather resistance and yellowing resistance than those of Examples 1-4;
[0075] Compared with Comparative Example 1, Example 2 shows that when tannic acid is replaced by levodopa and catechol, the weather resistance of the modified titanium dioxide decreases. This may be because the coupling system formed by the polydopamine film formed by levodopa and catechol and the silane coupling agent "3-glycidyloxypropyltriethoxysilane" is not stable enough compared to the coupling system of polytannic acid and 3-glycidyloxypropyltriethoxysilane, resulting in a decrease in the weather resistance of the final product.
[0076] Compared with Comparative Example 2, Example 2 shows that when 3-glycidyloxypropyl triethoxysilane is replaced by aminopropyl trimethoxysilane, the weather resistance of the final modified titanium dioxide is affected. This is because 3-glycidyloxypropyl triethoxysilane has more epoxy groups than aminopropyl trimethoxysilane, and the coupling system formed with polytannic acid during the coupling process is more stable.
[0077] It can be seen from Example 2 that compared with Comparative Examples 3-5, the configuration of nano-titanium dioxide, the microscopic size of titanium dioxide, the addition amount range of tannic acid-titanium dioxide, 3-glycidyloxypropyltriethoxysilane and nano-barium sulfate, and the microscopic size of nano-barium sulfate in the technical solution provided by the present invention are all key factors affecting the weather resistance of the modified titanium dioxide.
[0078] Finally, it should be noted that the above embodiments and comparative examples are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing highly weather-resistant titanium dioxide, characterized in that: The following steps are involved: S1. Mix nano-titanium dioxide and water to obtain a suspension, add a dispersant, and stir to mix evenly to obtain a titanium dioxide dispersion; S2. Tris(hydroxymethyl)aminomethane is dissolved in the titanium dioxide dispersion, and hydrochloric acid solution is slowly added and mixed until the pH of the titanium dioxide dispersion is adjusted to 8.5-9 to obtain a mixed titanium dioxide dispersion; S3. Take tannic acid and add it to the mixed titanium dioxide dispersion of step S2, stir at a temperature of 25-30 ° C, react for 12-24h, centrifuge solid-liquid separation, separate the solid residue A with water several times, vacuum dry, grind into powder to obtain tannic acid - titanium dioxide; S4. Take tannic acid-titanium dioxide and add it to an ethanol aqueous solution with a concentration of ≥95 v / v%, and add 3-glycidyloxypropyl triethoxysilane to dissolve evenly. At a temperature of 60-70 ° C, slowly add nano-barium sulfate and stir for 30-60 minutes. After completion, centrifuge the solid-liquid separation, and wash the separated solid slag B with water several times, vacuum dry, and grind into powder to obtain a modified high weather-resistant titanium dioxide; The mass ratio of the tannic acid-titanium dioxide, 3-glycidyloxypropyltriethoxysilane and nano-barium sulfate is 1:(0.2-0.5):(1.6-1.8).
2. The method for preparing highly weather-resistant titanium dioxide according to claim 1, characterized in that: The nano titanium dioxide is rutile titanium dioxide with a particle size of 200-300nm.
3. The method for preparing highly weather-resistant titanium dioxide according to claim 1 or 2, characterized in that: In step S1, nano titanium dioxide is mixed with water to obtain a suspension having a material-water ratio of 1.2-2.0 g / L, a dispersant is added in an amount of 0.6-1.0 g / L, and the mixture is stirred and mixed uniformly at room temperature and 200-300 r / min to obtain a titanium dioxide dispersion.
4. The method for preparing highly weather-resistant titanium dioxide according to claim 1 or 2, characterized in that: In the step S2, tris(hydroxymethyl)aminomethane is dissolved in the titanium dioxide dispersion at an addition amount of 1.0-1.2 g / L, and a hydrochloric acid solution with a concentration of 2.5-3.65 g / L is slowly added and mixed until the pH of the titanium dioxide dispersion is adjusted to 8.5-9.
5. The method for preparing highly weather-resistant titanium dioxide according to claim 1 or 2, characterized in that: In step S3, tannic acid is added to the mixed titanium dioxide dispersion in step S2 in an amount of 2-3 g / L, and stirred at a speed of 500-800 r / min and a temperature of 25-30° C. to react for 12-24 hours.
6. The method for preparing highly weather-resistant titanium dioxide according to claim 1 or 2, characterized in that: In the step S4, tannic acid-titanium dioxide is added to an ethanol aqueous solution with a concentration of ≥95 v / v%, at which the material-liquid ratio is 1.0-1.5 g / L, and 3-glycidyloxypropyltriethoxysilane is added. The mixture is stirred for 30-60 min at room temperature and a speed of 200 r / min to dissolve evenly. The speed is increased to 500 r / min, the temperature is increased to 60-70°C, and nano-barium sulfate is slowly added while stirring. After the addition is completed, the speed is increased to 1000 r / min, and stirring is continued for 30-60 min.
7. The method for preparing highly weather-resistant titanium dioxide according to claim 1 or 2, characterized in that: In steps S3 and S4, the water used in the multiple washings is deionized water, and the solid slag A is washed until the conductivity of the aqueous solution is ≤100 μS / cm, and the solid slag B is washed until the conductivity of the aqueous solution is ≤50 μS / cm.
8. The method for preparing highly weather-resistant titanium dioxide according to claim 3, characterized in that: The dispersant is at least one of sodium hexametaphosphate, sodium dihydrogen phosphate, calcium silicate and sodium silicate.
9. A highly weather-resistant titanium dioxide, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the highly weather-resistant titanium dioxide according to claim 9 in the preparation of coatings, paints and / or plastics with high weather resistance.
Citation Information
Patent Citations
Surface-modified, structurally modified titanium dioxides
CA2531556A1
Liquid titanium dioxide delustering agent for polyester and application
CN114106415A
PET assistant master batch as well as preparation method and application thereof
CN118388806A
Modified titanium dioxide
WO2009033877A2